Odpowiedź :
Odpowiedź:
[tex]19. \: a) \frac{2}{3} - \frac{5}{9} = \frac{6}{9} - \frac{5}{9} = \frac{1}{9} \\ b) \frac{5}{6} - \frac{3}{8} = \frac{20}{24} - \frac{9}{24} = \frac{11}{24} \\ c)1 \frac{1}{8} - \frac{3}{5} = 1 \frac{5}{40} - \frac{24}{40} = \frac{21}{40} \\ d)3 \frac{2}{9} - \frac{11}{12} = 3 \frac{8}{36} - \frac{33}{36} = 2 \frac{11}{36} \\ e)6 \frac{1}{7} - 2 \frac{2}{3} = 6 \frac{3}{21} - 2 \frac{14}{21} = 3 \frac{10}{21} \\ f)4 \frac{1}{12} - 1 \frac{3}{8} = 4 \frac{2}{24} - 1 \frac{9}{24} = 2 \frac{17}{24} [/tex]